Multi response optimization in wire electrical discharge machining of Inconel X-750 using Taguchi's technique and grey relational analysis. Issue 1 (31st December 2016) - Kumar, Mandeep; Singh, Hari
Abstract: The effective optimization of machining process parameters affects dramatically the cost and production time of machined components as well as the quality of the final products. This study presents an investigation on cutting speed and surface roughness of Inconel X-750 using Wire-cut electric discharge machining process. Six input process parameters of Wire-cut Electro Discharge Machining—spark gap voltage, pulse-on time, pulse-off time, wire feed rate, peak current and wire tension—were chosen to study their effects on the selected responses. Taguchi's design of experiments methodology has been used for planning, designing and conducting the experiments. The grey relational analysis has been applied in conjunction with the Taguchi's parameter design approach for the optimization of multiple responses. The analysis of variance has been applied to identify the significance of different parameters. Finally the confirmation experiments were performed to validate the predicted optimized results.